Sustained delivery fluocinolone acetonide vitreous inserts provide benefit for at least 3 years in patients with diabetic macular edema - Campochiaro, Peter A; Brown, David M; Pearson, Andrew; Chen, Sanford; Boyer, David; Ruiz-Moreno, Jose; Garretson, Bruce; Gupta, Amod; Hariprasad, Seenu M; Bailey, Clare; Reichel, Elias; Soubrane, Gisele; et al. (Ophthalmology (Rochester, Minn.), 2012)
To assess long-term efficacy and safety of intravitreal inserts releasing 0.2 μg/d (low dose) or 0.5 μg/d (high dose) fluocinolone acetonide (FAc) in patients with diabetic macular edema (DME). Two randomized, sham injection-controlled, double-masked, multicenter clinical trials. Subjects with persistent DME despite ≥1 macular laser treatment were randomized 1:2:2 to sham injection (n = 185), low-dose insert (n = 375), or high-dose insert (n = 393). Subjects received study drug or sham injection and after 6 weeks were eligible for rescue laser. Based on retreatment criteria, additional study drug or sham injections could be given after 1 year. Percentage of patients with improvement of ≥15 letters from baseline. Secondary outcomes included other parameters of visual function and foveal thickness. At month 36, the percentage of patients who gained ≥15 in letter score using the last observation carried forward method was 28.7% (low dose) and 27.8% (high dose) in the FAc insert groups compared with 18.9% (P = 0.018) in the sham group, and considering only those patients still in the trial at month 36, it was 33.0% (low dose) and 31.9% (high dose) compared with 21.4% in the sham group (P = 0.030). Preplanned subgroup analysis demonstrated a doubling of benefit compared with sham injections in patients who reported duration of DME ≥3 years at baseline; the percentage who gained ≥15 in letter score at month 36 was 34.0% (low dose; P<0.001) or 28.8% (high dose; P = 0.002) compared with 13.4% (sham). An improvement ≥2 steps in the Early Treatment Diabetic Retinopathy Study retinopathy scale occurred in 13.7% (low dose) and 10.1% (high dose) compared with 8.9% in the sham group. Almost all phakic patients in the FAc insert groups developed cataract, but their visual benefit after cataract surgery was similar to that in pseudophakic patients. The incidence of incisional glaucoma surgery at month 36 was 4.8% in the low-dose group and 8.1% in the high-dose insert group. In patients with DME FAc inserts provide substantial visual benefit for up to 3 years and would provide a valuable addition to the options available for patients with DME.